Social Capital: A Literature Review In Resources Management - Yusmar Yusuf; Meyzi Heriyanto; Tri Joko Waluyo; Syafrizal; Mashur Fadli; Achmad Fajri Febrian (International Journal of Educational Research & Social Sciences, 2021)
The subject of this study is resource management. By examining the literature that has the keyword "social capital" in the article title and a source region, the goal of this study is to identify research trends and research areas in the field of social capital in 2021, as well as publications from time to time and by nation (locus). The search was limited to Scopus-indexed publishers. To be used as research literature analysis material, the article must meet six inclusion criteria. A total of 120 articles were found to be related to the inclusion criteria and used as material for literary analysis in this study. The VOS Viewer Software is used in the SLR approach and there. The results of the SLR mapping in 2021 demonstrate that it is currently developing, and there are chances for social capital research with topics like cooperation, grassroots level, collaboration network, and supply chain collaboration. The scope of grassroots collaborative and social capital research is extremely vast, encompassing both technical and non-technical domains. Researchers from various countries are investigating how to bring changes in the business environment closer to the era of the digital economy and achieve a longterm competitive advantage in the field of technology, which is defined by traits such as technical mastery and innovation. This study's findings are remarkable.